Haemorrhage requiring embolisation after low energy pelvic fracture in an elderly patient: a case report. Issue 9 (26th August 2010) - Martin, Samuel; Casey, Nikki
Abstract : An 89-year-old woman presented with a stable fracture of the pelvis following a low energy trauma. The patient was taking no anticoagulation medication and was found to have life-threatening pelvic bleeding which required embolisation. Stable pelvic fractures following low energy trauma are common injuries in the elderly and frequently require admission for pain relief and mobility management. This case highlights that severe pelvic bleeding is a possible, life-threatening sequela after low energy pelvic injury in the elderly, and careful attention must be paid to the signs of active haemorrhage.